Extract of Dragon Fruit Pulp (Hylocereus polyrhizus) Potentially Stain Chromosomes of Red Onion (Allium ascalonicum) - Genesiska Genesiska; Herda Pratiwi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
Side effect of aceto-orcein as a dye of chromosome structures remains some risks. This dye may remain tissue damage on eyes mucous membrane, burnt by skin contact, severe irritation of respiratory by spray mist. Exploration of natural dye is an alternative solution. Betacyanine of red dragon fruits Hylocereus polyrhizus pulp might have a potential role to stain chromosome. Aim of this study is to extract dragon fruit pulp to stain chromosomes of mitotic cells of red onion Allium ascalonicum. The method used in this research is qualitative description of application squash method with aceto-orcein as synthetic dye and two ratio of extract ratio of red dragon fruits pulps as natural dye to mitotic cells of red onion roots. The result revealed that 2:1 ratio of red dragon fruits and distilled water could stain chromosomes of red onion somatic cells. Further specific solvent is required to further investigation to get best betacyanine extract of red dragon fruits pulps.